Assessment of residential battery storage systems and operation strategies considering battery aging. (8th November 2019) - Förstl, Markus; Azuatalam, Donald; Chapman, Archie; Verbič, Gregor; Jossen, Andreas; Hesse, Holger
Summary: With the increasing popularity of combining residential photovoltaic systems with battery storages, research, industry, and customers look for ways to determine if such an investment is economically profitable. Simulation programs may serve to predict the profitability and lifetime of the system. In this paper, we use techno‐economic analysis with a specific account of battery degradation to determine profitability and lifetime of a residential photovoltaic (PV) battery system under different energy management and tariff regimes. This work presents two case studies: the first being a techno‐economic comparison for a residential PV‐battery system in New South Wales, Australia and Germany, and the second analyzing the profitability and degradation impact of three different operation strategies for a battery storage in Australia. The results reveal that site‐specific conditions (i.e., geographical and energy‐economic constraints) may have a significant impact on the ideal system configuration and ultimately the anticipated battery lifetime. Furthermore, statistical analysis of different storage operation strategies applied to various prosumer load and generation profiles reveals the effects of storage dispatch strategies on battery aging. Abstract : Our paper reveals the effects of different geographic and economic framework conditions on the technical and economic performance of residential battery storage systems. Furthermore, we make a strong point for considering aging mechanisms when developing heuristic and optimized battery operation strategies, since algorithms with favorable economic performance can significantly shorten battery lifetime.